Application of electric resistance method in characterizing the ability of load transfer of interphase in single-fiber composite. (March 2016) - Sun, Xinyang; Hu, Jianqian; Zhang, Boming
In this paper, the tensile property of single T300 carbon fiber accompanied by the relationship between the electric resistance and the strain was tested. The collected data showed that there was a linear relationship between them. Then its coefficient of sensitivity K was acquired by computation. Next, two-dimensional loading platform was built to load the tilted cross samples in tension and the stress distribution under loading was observed through an optical microscope synchronistically. Based on the above results, the resistance method was combined with tilted cross model, the above coefficient of sensitivity was used to confirm the shearing stress of the interphase in the tilted cross model, the coefficient of sensitivity was combined to confirm the differences in stress transfer in this system, and numerical analysis was utilized to confirm the performance parameter of the cohesive interphase element in the numerical model of this system.